2019
DOI: 10.15244/pjoes/89507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Platinum, Rhodium, and Palladium Bioaccumulation by Sinapis alba and their Influence on Phytochelatin Synthesis in Plant Tissues

Abstract: Phytochelatins are known to play an essential role in xenobiotic detoxification in some plants. Until now, their synthesis in plants exposed to platinum group elements (PGEs), especially Pd and Rh, has not been directly proven. The influence of PGEs on the natural environment, especially on living organisms, is particularly important in view of increasing emissions of these elements from automotive catalytic converters. This paper describes studies related to the identification of the presence of phytochelatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…In addition, the Gibbs free energy of formation (∆G) values for PtS, PdS, and Rh 2 S 3 , at standard state conditions, as they are given from the experimental data [34,35] and calculations [36], are −66 kj/moll for PdS, −76 kj/mol for PtS, and −252 kj/mol for Rh 2 S 3 . The more negative Gibbs free energy values for the Rh 2 S 3 compared to those for the PdS and PtS seem to be in good agreement with the lower availability and the lower Rh content in plants (Table 2) and in shoots than in the roots [21]. Thermodynamic properties have also been applied to explain the difference in mobility between Au and Pt [37].…”
Section: Geochemical Characteristicssupporting
confidence: 53%
See 3 more Smart Citations
“…In addition, the Gibbs free energy of formation (∆G) values for PtS, PdS, and Rh 2 S 3 , at standard state conditions, as they are given from the experimental data [34,35] and calculations [36], are −66 kj/moll for PdS, −76 kj/mol for PtS, and −252 kj/mol for Rh 2 S 3 . The more negative Gibbs free energy values for the Rh 2 S 3 compared to those for the PdS and PtS seem to be in good agreement with the lower availability and the lower Rh content in plants (Table 2) and in shoots than in the roots [21]. Thermodynamic properties have also been applied to explain the difference in mobility between Au and Pt [37].…”
Section: Geochemical Characteristicssupporting
confidence: 53%
“…For example, 8 µg/kg Pt, 25 µg/kg Pd, and 5.5 µg/kg Rh in shoots, and 762 µg/kg Pt, 663 µg/kg Pd, and 437 µg/kg Rh in tree leaves have been noted [21]. In addition, cultivated plants, using Rh salt, have shown as high as 650-1300 accumulation factors for roots and much lower (7) for stems leaves (4) [21].…”
Section: Geochemical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these conditions, the accumulated Pd triggered the synthesis of total thiol-containing proteins for metal stress tolerance. Previous studies showed that several metals had activated the synthesis of enzymes such as the phytochelatin synthetase to produce phytochelatins (PCs), permitting control of the intracellular concentration of metals (Supalkova et al 2007;Yao et al 2012;Kińska and Kowalska 2019).ńKińska and Kowalska (2019) detected the synthesis of PC 2 , PC 3 , and PC 4 in leaf tissues of the white mustard Sinapis alba L. cultivated in nutrient solution containing 1 mg/L of PdCl 2 . In the present study, the synthesis of phytochelatins was activated in Pd-treated L. minor plants, but more analysis is needed to quantify the induction of phytochelatins.…”
Section: Activation Of Defense Mechanisms Under Pd Stressmentioning
confidence: 99%